2022
DOI: 10.36469/jheor.2022.33801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Healthcare Resource Utilization for Patients with Mucopolysaccharidosis II (MPS II) in the United States: A Retrospective Chart Review

Abstract: Background: Mucopolysaccharidosis II (MPS II; Hunter syndrome) is a rare, X-linked, life-limiting lysosomal storage disease characterized by a deficiency in the activity of the enzyme iduronate-2-sulfatase. Accumulation of glycosaminoglycans in tissues and organs throughout the body causes cellular damage, leading to multisystemic disease manifestations. Patients generally require multidisciplinary care across a wide range of specialties. Objectives: The aims of this study were to assess the healthcare needs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
(47 reference statements)
2
14
0
1
Order By: Relevance
“…24,25 The clinical needs and HRU of 140 patients with MPS II were previously evaluated in a retrospective chart review performed in the United States over a 20-year period (1997-2017). 23 This study showed that both disease burden and HRU in these patients are high. 23 Furthermore, the clinical burden and HRU were shown to be similar between patients who received ERT with IV idursulfase (n = 108) and those who had never received ERT (n = 32); however, this comparison was limited by the heterogeneity of the patient population.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…24,25 The clinical needs and HRU of 140 patients with MPS II were previously evaluated in a retrospective chart review performed in the United States over a 20-year period (1997-2017). 23 This study showed that both disease burden and HRU in these patients are high. 23 Furthermore, the clinical burden and HRU were shown to be similar between patients who received ERT with IV idursulfase (n = 108) and those who had never received ERT (n = 32); however, this comparison was limited by the heterogeneity of the patient population.…”
Section: Introductionmentioning
confidence: 69%
“…23 This study showed that both disease burden and HRU in these patients are high. 23 Furthermore, the clinical burden and HRU were shown to be similar between patients who received ERT with IV idursulfase (n = 108) and those who had never received ERT (n = 32); however, this comparison was limited by the heterogeneity of the patient population. 23 To inform healthcare decision-making, there is a need for greater understanding of the influence of timing of ERT initiation and CI status on the outcomes of patients with MPS II.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations